2022
DOI: 10.1021/acs.macromol.1c02599
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility and Thermal and Structural Properties of Poly(l-lactide)/Poly(l-co-d-lactide) Blends

Abstract: To explicate the interaction processes between poly­(l-lactide) (PLLA) and poly­(l-co-d-lactide) (PLDLA) in their blends, a series of high-molecular-weight PLDLA-m polymers (where m represents the percentage of l-lactate units) were prepared by ring-opening polymerization at different feed ratios of l- to d-lactides and blended with highly optically pure PLLA by solution blending. The compatibility and thermal and structural properties of the PLLA/PLDLA-m blends were investigated by differential scanning calor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Its thermal resistance is limited by a relatively low heat deflection temperature due to the slow crystallization and low crystallizability in practical processing such as injection molding. , It is worth mentioning that the presence of chiral carbon in the skeletal chain of PLA results in two stereoregular enantiomers, namely poly­( l -lactide) (PLLA)­and poly­( d -lactide) (PDLA). The PLLA /PDLA racemic blends lead to the formation of SCs with denser chain packing and stronger interchain interactions. The chemical and physical properties of the stereocomplex poly­(lactic acid) (sc-PLA) strongly exceed those of its parent enantiomeric pure, homocrystalline polymers, such as higher mechanical strength, better thermal stability, lower thermodegradation, etc. Meanwhile, this specific complex structure can effectively solve the above-mentioned limitations. Since this first report, the influences of the homopolymer molecular weight, blending ratio, blending conditions, and optical purity on the formation and properties of stereocomplexes have been well investigated. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its thermal resistance is limited by a relatively low heat deflection temperature due to the slow crystallization and low crystallizability in practical processing such as injection molding. , It is worth mentioning that the presence of chiral carbon in the skeletal chain of PLA results in two stereoregular enantiomers, namely poly­( l -lactide) (PLLA)­and poly­( d -lactide) (PDLA). The PLLA /PDLA racemic blends lead to the formation of SCs with denser chain packing and stronger interchain interactions. The chemical and physical properties of the stereocomplex poly­(lactic acid) (sc-PLA) strongly exceed those of its parent enantiomeric pure, homocrystalline polymers, such as higher mechanical strength, better thermal stability, lower thermodegradation, etc. Meanwhile, this specific complex structure can effectively solve the above-mentioned limitations. Since this first report, the influences of the homopolymer molecular weight, blending ratio, blending conditions, and optical purity on the formation and properties of stereocomplexes have been well investigated. …”
Section: Introductionmentioning
confidence: 99%
“… 7 10 The chemical and physical properties of the stereocomplex poly(lactic acid) (sc-PLA) strongly exceed those of its parent enantiomeric pure, homocrystalline polymers, such as higher mechanical strength, better thermal stability, lower thermodegradation, etc. 11 13 Meanwhile, this specific complex structure can effectively solve the above-mentioned limitations. Since this first report, the influences of the homopolymer molecular weight, blending ratio, blending conditions, and optical purity on the formation and properties of stereocomplexes have been well investigated.…”
Section: Introductionmentioning
confidence: 99%
“…4 proposes a mechanism of the competing polymorphic crystallization in SC-PLA. On one hand, separation of racemic segments may occur due to their thermodynamic immiscibility [44][45][46], or due to the kinetically favored HC crystallization [47]. On the other hand, at the same time, due to thermal fluctuation, the racemic segments can be paired by hydrogen bonding that leans towards SC nucleation [42,48].…”
Section: Competing Crystallization Behavior Of Nanocompositesmentioning
confidence: 99%
“…The chemical and physical properties of SC PLA strongly exceed those of its parent enantiomeric pure, homocrystalline polymers, such as higher mechanical strength, better thermal stability, lower thermodegradation, etc. 20,21 For example, the blending of PLLA and PDLA can result in the formation of SCs with a melting point of about 50 °C higher than that of homocrystals (HCs). 22−24 As a biocompatible and flexible polymer, poly(ethylene glycol) (PEG) is a good candidate for modification of PLA toughness through physical blending.…”
Section: Introductionmentioning
confidence: 99%
“…Since Y. Ikada proposed the stereocomplex (SC) crystallization of PLLA and PDLA in 1987, a large number of studies on the formation of the SC have been reported. The chemical and physical properties of SC PLA strongly exceed those of its parent enantiomeric pure, homocrystalline polymers, such as higher mechanical strength, better thermal stability, lower thermodegradation, etc. , For example, the blending of PLLA and PDLA can result in the formation of SCs with a melting point of about 50 °C higher than that of homocrystals (HCs). …”
Section: Introductionmentioning
confidence: 99%